The influence of the addition of granulated sugar on the organoleptic quality of dendeng ground meet deer (Cervus timorensis) - Seseray, Daniel Y.; Jandit, Oktovianus; Monim, Hanike; Chrysostomus, Hieronymus Y.; Randa, John S.; Sumpe, Iriani; Pawere, Frandz R.; Yoku, Onesimus; Indey , Seblum (Fakultas Peternakan Universitas Papua, 2025)
This study evaluated sucrose at concentrations of 0, 5, 10, 15, and 20% (w/w) in ground deer meat dendeng (DGDR) to inform SME-oriented formulation. The products were dried at 60°C for 24 hours. They were then assessed by 30 semi-trained panelists (1–5 hedonic) in a within-panelist repeated-measures design. Ordinal data were analyzed using a Friedman omnibus test with Holm-adjusted Wilcoxon signed-rank comparisons. Results are reported as medians. The color increased significantly at ≥10% compared to 0%. Taste improved with sugar, producing a smoother sweet–spice balance. Aroma remained characteristic across levels. Tenderness showed a non‑significant softening at ≥15%. Overall acceptability increased with sugar, with 10–20% exceeding the control (p < 0.05). Five percent showed a trend upward, indicating an early plateau at 5% or higher. Sucrose thus functions as a practical lever to elevate appearance and liking without compromising aroma under the specified process. A formulation of 12–15% is recommended as the default. Levels of 15–20% suit markets seeking darker colors and slightly sweeter profiles. Future work should pair hedonic outcomes with instrumental measurements of color, texture, and volatility. It should also include shelf-life studies and evaluate clean-label preservation options or partial sucrose substitution.